Life Cycle Assessment of the production of avocado in Peru - (:unkn) unknown (My University, 2026)
Currently, EXPANSCIENCE is interested in exploring the environmental profile of the production of avocado from Peru, in order to improve the environmental performance throughout its supply chain, including mitigation of greenhouse gas emissions and other